Prosocial Behavior Prediction in the Elderly Based on the Relationship with God and Demographic Characteristics - abdollah moatamedi (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2019)
The aim of the research was studying the prosocial behavior in old age to investigate the role of relationship with God and demographic characteristics of the elderly adult. Prosocial behavior is any behavior that is socially constructive or helpful in some way to another person or group. Prosocial behavior in Islam is different instances, so maintaining a relationship with God on prosocial behavior imaginable. The present study is a descriptive and correlational research which was implemented in 1396. The population of the study were elderly (those 60 and older) living in Tehran. Of the population 338 persons as the sample, in the way of multistage sampling were selected. The research tools include: 1. Pener Inventory of prosocial personality (PSB) and 2- God relationship Questionnaire. After analyzing the data using ANOVA test and Regression test, the results showed that those who had a weak relationship with God than those with high relevance or even moderate relationship with God, had a lower prosocial behavior. Also, when in the form of a regression model the effect of different variables on the prosocial behavior was studied, it was observed that variables such as gender, age and occupation had no significant effect on prosocial behavior while relationship with God and education had a significant effect on prosocial behavior. This also means that those who have a stronger relationship with God and have higher levels of education have a more prosaical behavior.